The Effect of Indonesian Anti-Dating Movement (Gitp) on Early Marriage - Ilham Andika Putra; Sulaiman Sulaiman (International Journal Of Education, Social Studies, And Management (IJESSM), 2023)
In order to improve the morals of the younger generation of Islam, many organizations have sprung up that target teenagers to migrate so that a youth movement has formed to act as agents of change. This organization is able to influence of Islamic youth, with the methods of delivery and the style of the preachers who are very up-to-date, and they often carry out da'wah via social media, so that they can increase the closeness between the congregation and the preachers. This research used a qualitative method was chosen in this study with a literature study approach to see the influence of the Indonesian movement anti-dating on early marriage through research analysis that had been carried out by previous researchers and then explained in a narrative. Based on the results of GITP's research, it is very influential and useful to be an agent of change in instilling noble characters or morals in young Muslims. This organization influences early marriage with the Indonesian movement without dating. The aim of this movement is very positive so that young people can avoid adultery, but the understanding of the preachers and congregations who are still not in this movement makes the practice of early marriage even more prevalent. To prevent this, it is necessary to provide counseling and awareness to the younger generation regarding the dangers of early marriage or marriage at a young age as well as supervision and collaboration with hijrah youth organizations.